Metabolomic Analysis by Nuclear Magnetic Resonance Spectroscopy as a New Approach to Understanding Inflammation and Monitoring of Pharmacological Therapy in Children and Young Adults With Cystic Fibrosis - Montuschi, Paolo; Lucidi, Vincenzina; Paris, Debora; Montemitro, Enza; Shohreh, Rugia; Mores, Nadia; Melck, Dominique; Santini, Giuseppe; Majo, Fabio; Motta, Andrea (Frontiers in Pharmacology, 2018)
15-F2t-Isoprostane, a reliable biomarker of oxidative stress, has been found elevated in exhaled breath condensate (EBC), a non-invasive technique for sampling of airway secretions, in patients with cystic fibrosis (CF). Azithromycin has antioxidant properties in experimental models of CF, but its effects on oxidative stress in CF patients are largely unknown. Primary objective of this pilot, proof-of-concept, prospective, parallel group, pharmacological study, was investigating the potential antioxidant effects of azithromycin in CF patients as reflected by EBC 15-F2t-isoprostane. Secondary objectives included studying the effect of azithromycin on EBC and serum metabolic profiles, and on serum 15-F2t-isoprostane. In CF patients who were on maintenance treatment with oral vitamin E (200 UI once daily), treatment with oral azithromycin (250 or 500 mg depending on body weight) plus vitamin E (400 UI once daily) (group A) (n = 24) or oral vitamin E alone (400 UI once daily) (group B) (n = 21) was not associated with changes in EBC 15-F2t-isoprostane compared with baseline values after 8–week treatment or 2 weeks after treatment suspension. Likewise, no within- or between-group differences on serum 15-F2t-isoprostane or metabolites were observed in both study groups. NMR spectroscopy-based metabolomics of EBC shows that suspension of both azithromycin plus vitamin E and vitamin E alone has a striking effect on metabolic profiles in EBC. Between-group comparisons show that EBC metabolite distribution after treatment and two weeks after treatment suspension is different. Quantitative differences in ethanol, saturated fatty acids, acetate, acetoin/acetone, and methanol are responsible for these differences. Our study was unable to show antioxidant effect of azithromicyn as add-on treatment with doubling the dose of oral vitamin E as reflected by 15-F2t-isoprostane concentrations in EBC. Add-on therapy with azithromycin itself does not induce EBC metabolite changes, but its suspension is associated with EBC metabolic profiles that are different from those observed after vitamin E suspension. The pathophysiological and therapeutic implications of these findings in patients with stable CF are unknown and require further research. Preliminary data suggest that EBC NMR-based metabolomics might be used for assessing the effects of pharmacological treatment suspension in stable CF patients.